Antarctic Futures: An Assessment of Climate-Driven Changes in Ecosystem Structure, Function, and Service Provisioning in the Southern Ocean - Rogers, Alex David; Frinault, Betina A V; Barnes, D K A; Bindoff, Nathaniel Lee; Downie, Rod; Ducklow, Hugh W; Friedlaender, A S; Hart, T; Hill, Simeon; Hofmann, E E; Linse, Katrin; McMahon, Clive R; et al. (Annual Review of Marine Science, 2020)
In this article, we analyze the impacts of climate change on Antarctic marine ecosystems. Observations demonstrate large-scale changes in the physical variables and circulation of the Southern Ocean driven by warming, stratospheric ozone depletion, and a positive Southern Annular Mode. Alterations in the physical environment are driving change through all levels of Antarctic marine food webs, which differ regionally. The distributions of key species, such as Antarctic krill, are also changing. Differential responses among predators reflect differences in species ecology. The impacts of climate change on Antarctic biodiversity will likely vary for different communities and depend on species range. Coastal communities and those of sub-Antarctic islands, especially range-restricted endemic communities, will likely suffer the greatest negative consequences of climate change. Simultaneously, ecosystem services in the Southern Ocean will likely increase. Such decoupling of ecosystem services and endemic species will require consideration in the management of human activities such as fishing in Antarctic marine ecosystems.
Keywords: Sørishavet; biodiversitet; klimaendringer; marine økosystemer; miljøpåvirkning

The Committee for Environmental Protection: Its Establishment, Operation and Role within the Antarctic Treaty System - Orheim, Olav (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; miljø; miljøkonsekvensanalyser; miljøpåvirkning

The place of regulation in relation to science - Orheim, Olav (Changing trends in Antarctic research, 1993)
Keywords: Antarktis; miljø; miljøkonsekvensanalyser; miljøpåvirkning